An Analysis of May Month (2017-2019) Blood Pressure Screenings in Niger: A Case Study - Touré, Ali I.; Boubacar, Dodo; Ismael, Oumarou Y.; Souley, Kimba; Bonkano, Ali S.; Ousseini, Moustapha; Mossi, Dari; Issoufou, Garba I.; Souna, Moussa; Bonkano, Ousseina; Majid, Abdoul; Douma, Halima; et al. (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
In 2007, the prevalence of high blood pressure (BP) was 36% in Niger according to a recent survey by the World Health Organization (WHO). Niger got involved in the May Measurement Month (MMM) campaign in 2017, 2018, and 2019 to gain an understanding of the prevalence of selected cardiovascular risk factors and high BP. The aim of this study was to screen for cardiovascular risk factors with particular focus on high blood pressure (BP) in Niger and thereby to raise awareness among the population of Niger about raised BP and the associated risk to health. The city of Niamey served as our study location during the month of May in 2017, 2018, and 2019. Volunteer adults aged \(\ge\)18 years, who completed a pre-established questionnaire were screened and had three sitting BP measurements taken. Hypertension was defined as a systolic BP \(\ge\)140 mmHg or diastolic BP \(\ge\)90 mmHg (based on the mean of the second and third BP readings) or being on antihypertensive medication. In this study, 2297 adults were screened, of which 42.9% were women and 57.1% were men. Of the 2297 screened, 33.2% were found to be hypertensive of whom only 26 (3.4%) were recorded as being on treatment. Approximately 30% of those screened were found to be obese or overweight. The MMM campaign in Niger highlights a large number of people with hypertension can be screened opportunistically. In the absence of systematic and population-based screening, the MMM campaign should be continued annually in order to raise awareness of raised BP and its complications among the population. High BP is a real public health danger, and this study finds alarming figures that highlight the need for improved policies for screening and management of hypertension. Raising awareness and improving the detection of hypertension remain essential to reduce the burden of cardiovascular disease.